Answer:
![f(x) = 3(x -\frac{2}{3})^2 -\frac{22}{3}](https://tex.z-dn.net/?f=f%28x%29%20%3D%203%28x%20-%5Cfrac%7B2%7D%7B3%7D%29%5E2%20-%5Cfrac%7B22%7D%7B3%7D)
The vertex is ![(\frac{2}{3}, -\frac{22}{3})](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B3%7D%2C%20-%5Cfrac%7B22%7D%7B3%7D%29)
Step-by-step explanation:
For a general quadratic function the form is:
![ax ^ 2 + bx + c](https://tex.z-dn.net/?f=ax%20%5E%202%20%2B%20bx%20%2B%20c)
For the function
![f(x) = 3x ^ 2 -4x -6](https://tex.z-dn.net/?f=f%28x%29%20%3D%203x%20%5E%202%20-4x%20-6)
Take common factor 3.
![f(x) = 3(x ^ 2 -\frac{4}{3}x - 2)](https://tex.z-dn.net/?f=f%28x%29%20%3D%203%28x%20%5E%202%20-%5Cfrac%7B4%7D%7B3%7Dx%20-%202%29)
The values of the coefficients for the function within the parenthesis are the following:
,
, ![c = -2](https://tex.z-dn.net/?f=c%20%3D%20-2)
Take the value of b and divide it by 2. Then, the result obtained squares it.
![\frac{b}{2}= -\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%7D%7B2%7D%3D%20-%5Cfrac%7B2%7D%7B3%7D)
![(\frac{b}{2})^2=\frac{4}{9}](https://tex.z-dn.net/?f=%28%5Cfrac%7Bb%7D%7B2%7D%29%5E2%3D%5Cfrac%7B4%7D%7B9%7D)
Add and subtract ![\frac{4}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B9%7D)
![f(x) = 3([x ^ 2 -\frac{4}{3}x +\frac{4}{9}]- 2-\frac{4}{9})](https://tex.z-dn.net/?f=f%28x%29%20%3D%203%28%5Bx%20%5E%202%20-%5Cfrac%7B4%7D%7B3%7Dx%20%2B%5Cfrac%7B4%7D%7B9%7D%5D-%202-%5Cfrac%7B4%7D%7B9%7D%29)
Write the expression of the form
![f(x) = (x-\frac{b}{2})^2 +k](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x-%5Cfrac%7Bb%7D%7B2%7D%29%5E2%20%2Bk)
![f(x) = 3(x -\frac{2}{3})^2 -\frac{22}{3}](https://tex.z-dn.net/?f=f%28x%29%20%3D%203%28x%20-%5Cfrac%7B2%7D%7B3%7D%29%5E2%20-%5Cfrac%7B22%7D%7B3%7D)
The vertex is ![(\frac{2}{3}, -\frac{22}{3})](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B3%7D%2C%20-%5Cfrac%7B22%7D%7B3%7D%29)
Answer:
67. A
68. D
Step-by-step explanation:
I don't remember exactly the explanation, but I recommend you try to learn more about number lines sometime when you aren't under stress from schoolwork, because they're pretty simple questions to answer once you get a better understanding of them!
Because it means it has two answers when -8×-8 it equals 64 so is 8×8
in math when negative multiply negative it will be positive...
Answer is B. No matter what the x or y will be the result will be 0. Anything multiplied by 0 is equal to 0.